COMPARING OUTCOMES OF PERCUTANEOUS CORONARY INTERVENTION OF NATIVE ARTERY VERSUS BYPASS GRAFT IN PATIENTS WITH PRIOR CORONARY ARTERY BYPASS GRAFTING : A SYSTEMATIC REVIEW - Tria Fadilla, Annisa; Tri Sutrisno, Reza; Arifin Rambe, Zainal; Namora Siregar, Aulia Doli; Syahroni Nasution, Faisal; Sabri, Muhammad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Percutaneous coronary intervention (PCI) is common in patients with prior coronary artery bypass graft surgery (CABG), however the data on the association between the PCI target-vessel and clinical outcomes are not clear. We aimed to investigate long-term clinical outcomes of patients with prior CABG who underwent PCI of either bypass graft or native artery. We performed a systematic review of observational studies comparing PCI of either bypass graft or native artery in patients with prior CABG. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 23 articles, whereas the results of our search on SagePub brought up 19 articles. The results of the search conducted for the last year of 2013 yielded a total 9 articles for PubMed and 5 articles for SagePub. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion:  Most PCIs performed in prior CABG patients are done in native coronary artery lesions. Compared with native coronary PCI, bypass graft PCI is independently associated with higher in-hospital mortality.